A Conversation with John C. Gower. (27th February 2015) - Cox, David R.
Summary: Editors' Note: This conversation covers the extensive contributions of John C. Gower to statistical methodology, computing and applications. It also touches on the pioneering development of statistical computing at Rothamsted Experimental Station and the relevant work of Frank Yates, John Nelder and others who were at Rothamsted. See also the accompanying paper by John Gower (1985) on developments in statistical computing at Rothamsted (see Note 1) and the epilogue from Roger Payne.